X-band low phase noise quadrature CMOS VCO with transformer feedback - Liao, Yu-Shun; Jou, Christina F. (My University, 2008)
A fully integrated quadrature VCO with transformer feedback is proposed to achieve low-phase-noise and at a x-band using a TSMC 0.18-mu m CMOS technology. The VCO is implemented using a transformer-based LC tank and the transformer feedback configuration from the drain to the back-gate of the switching transistors. The simulation result shows the phase noise is about -114dBc/Hz at 1MHz offset and the output frequency tuning range of the QVCO is around 800 MHz ranging from 8.9 to 9.7 GHz. The QVCO core circuit draws only 4.1 mA from a 1.5-V supply. Compared with the recent works, the proposed QVCO topology shows phase noise performance 5 dBc/Hz lower than the original and power consumption of 6.15 mW compared to the original VCO core of 6.8 mW.